2018
DOI: 10.18203/2349-2902.isj20180821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low level laser therapy on diabetic foot ulcers: a randomized control trial

Abstract: Background: Nearly 15% of diabetic patients will suffer from DFU in their life span. Conventional treatment is not effective against the non-healing DFUs so in recent days so many adjuvant therapies which have been tried to stimulate healing process are in use. LLLT, is a non-invasive, pain-free method is considered as a possible treatment option for the diabetic foot syndrome. Aim of this study is to study the role of low level laser therapy on diabetic ulcers, i.e. Reduction in size of the ulcer, faster woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Therefore, laser therapy, specifically Low-Level Laser Therapy (LLLT), has been used as an adjuvant to conventional treatment to aid in wound tissue repair since it reduces the inflammatory process, favors recapillarization and neoformation of tissue layers, besides increasing collagen and elastic fibers in the healed area (13)(14)(15)(16) . In this perspective, some randomized studies show, through the evaluation of clinical indicators, tissue regeneration and reduction in the size of chronic lesions (vascular and diabetic) when using this type of adjuvant therapy to conventional treatment (17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, laser therapy, specifically Low-Level Laser Therapy (LLLT), has been used as an adjuvant to conventional treatment to aid in wound tissue repair since it reduces the inflammatory process, favors recapillarization and neoformation of tissue layers, besides increasing collagen and elastic fibers in the healed area (13)(14)(15)(16) . In this perspective, some randomized studies show, through the evaluation of clinical indicators, tissue regeneration and reduction in the size of chronic lesions (vascular and diabetic) when using this type of adjuvant therapy to conventional treatment (17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of people with DM will suffer from foot ulcers in their lifetime, where conventional treatments such as daily cleansing and dressing with 0.9% saline solution, essential fatty acids, hydrogel and betadine solution have shown little success in progressing tissue repair, with a higher rate of complications [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…A cohort of 1055 people with DM in 19 specialized centers in Brazil showed that 24.2% had previous foot ulcer and 13.7% prior amputation, and out of these, 5.3% had more than one amputation 8 . Thus, in recent years, adjuvant therapies have been tested to stimulate the wound healing process in people with DM 5 . Among the new therapies, low-level laser therapy (LLLT) is considered a noninvasive, painless, low-cost and effective method of wound treatment, as it acts on the physiological and biochemical events of the healing process [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Aproximadamente 15% das pessoas com DM sofrerão com úlceras nos pés em sua vida útil, em que os tratamentos convencionais, como limpeza e curativo diário com soro fisiológico 0,9%, ácidos graxos essenciais, hidrogel e solução de betadina demonstraram pouco sucesso no progresso do reparo tecidual, com maior índice de complicações [5][6][7] .…”
Section: Introductionunclassified
“…Uma coorte realizada com 1055 pessoas com DM em 19 centros especializados no Brasil evidenciou que 24,2% apresentavam úlcera prévia nos pés e 13,7% amputação anterior, e, destes, 5,3% possuíam mais de uma amputação 8 . Assim, nos últimos anos, terapias adjuvantes foram testadas para estimular o processo de cura de feridas em pessoas com DM 5 . Entre as novas terapias, a laserterapia de baixa intensidade (LBI) é apontada como um método não invasivo, indolor, de baixo custo e com eficácia no tratamento de feridas, por atuar nos eventos fisiológicos e bioquímicos do processo de cicatrização [9][10][11] .…”
Section: Introductionunclassified